Morbidity and Mortality in Heart Transplant Candidates Supported With Mechanical Circulatory Support: Is Reappraisal of the Current United Network for Organ Sharing Thoracic Organ Allocation Policy Justified? - Wever-Pinzon, Omar (2012)
BACKGROUND: Survival of patients on left ventricular assist devices (LVADs) has improved. We examined the differences in risk of adverse outcomes between LVAD-supported and medically managed candidates on the heart transplant waiting list. METHODS AND RESULTS: We analyzed mortality and morbidity in 33 073 heart transplant candidates registered on the United Network for Organ Sharing (UNOS) waiting list between 1999 and 2011. Five groups were selected: patients without LVADs in urgency status 1A, 1B, and 2; patients with pulsatile-flow LVADs; and patients with continuous-flow LVADs. Outcomes in patients requiring biventricular assist devices, total artificial heart, and temporary VADs were also analyzed. Two eras were defined on the basis of the approval date of the first continuous-flow LVAD for bridge to transplantation in the United States (2008). Mortality was lower in the current compared with the first era (2.1%/mo versus 2.9%/mo; P<0.0001). In the first era, mortality of pulsatile-flow LVAD patients was higher than in status 2 (hazard ratio [HR], 2.15; P<0.0001) and similar to that in status 1B patients (HR, 1.04; P=0.61). In the current era, patients with continuous-flow LVADs had mortality similar to that of status 2 (HR, 0.80; P=0.12) and lower mortality compared with status 1A and 1B patients (HR, 0.24 and 0.47; P<0.0001 for both comparisons). However, status upgrade for LVAD-related complications occurred frequently (28%) and increased the mortality risk (HR, 1.75; P=0.001). Mortality was highest in patients with biventricular assist devices (HR, 5.00; P<0.0001) and temporary VADs (HR, 7.72; P<0.0001). CONCLUSIONS: Mortality and morbidity on the heart transplant waiting list have decreased. Candidates supported with contemporary continuous-flow LVADs have favorable waiting list outcomes; however, they worsen significantly once a serious LVAD-related complication occurs. Transplant candidates requiring temporary and biventricular support have the highest risk of adverse outcomes. These results may help to guide optimal allocation of donor hearts.